2020
DOI: 10.1111/nyas.14329
|View full text |Cite
|
Sign up to set email alerts
|

Current status of immunotherapies for addiction

Abstract: The treatment of substance use disorders has always been challenging because multiple neurotransmitters mediate addiction. However, with smoking being the leading cause of preventable death and the recent opioid epidemic in the United States, the search for novel solutions becomes more imperative. In this review, we discuss the use of antibodies to treat addictions and highlight areas of success and areas that require improvement, using examples from cocaine, nicotine, and opioid vaccines. Through each example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…In the phase 2 trial NCT00318383 (n = 313), the vaccine was administered using two different formulations and dosing schedules to determine which generated the highest antibody levels. This proof-of-concept-study showed that participants with high antibody response were more likely to abstain from smoking than participants who received placebo [27].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In the phase 2 trial NCT00318383 (n = 313), the vaccine was administered using two different formulations and dosing schedules to determine which generated the highest antibody levels. This proof-of-concept-study showed that participants with high antibody response were more likely to abstain from smoking than participants who received placebo [27].…”
Section: Discussionmentioning
confidence: 87%
“…The phase 2 trial NCT00218413 (n = 51) assessed safety and antibody levels for varying vaccine doses. [27] states "increased abstinence related to Ab titer in phase II proof-ofconcept". Despite the study completion date of August 2006, the published study results were unable to be located [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaccines are a promising approach for the treatment of SUD [ 93 ]. SUD vaccines work by initiating the production of drug-specific antibodies that rapidly bind to the drug of abuse.…”
Section: Nanoparticle-based Treatments For Sudmentioning
confidence: 99%